Is the European Union Deforestation Regulation WTO-proof? - Bruno Capuzzi (European Centre for International Political Economy (ECIPE), 2024)
The European Union Deforestation Regulation (EUDR) is set to take effect on 30th December 2024. While it aligns with EU's climate goals under the European Green Deal, it has sparked concerns with EU partners regarding its compatibility with World Trade Organization (WTO) principles. Internally, some memberStates and productive sectors fear that the lack of clarity in its rules could disrupt European supply chains. Products like coffee, chocolate, and leather are some examples where costs and price are expected to rise due to compliance requirements, documentation, and shipment segregation. Critics argue that the EUDR's unilateral imposition of EU standards on third countries could be viewed as extraterritorial and more restrictive than necessary towards its objectives. This paper analyses lessons from WTO reports on US Shrimp/Turtle and US Tuna/Dolphin, which are relevant to discussions on nonproduct-related processes and production methods (PPMs). Key findings suggest that the EUDR could be justified under GATT exceptions clause (Article XX). However, for this to be successful, the Policy Brief proposes more flexibility in considering local realities of exporting countries. This would include shifting the EUDR approach to cooperating towards an outcome-based equivalence systems instead of rigid procedural requirements.
Keywords: 330